Legal regulation of artificial intelligence in Ukraine and in the world - Muravska , Yuliia; Slipchenko , Tetiana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article is devoted to the study of the concept of «artificial intelligence» which is the object of legal regulation and is an important element of modern development of intellectual and information security global system. The relevance of this scientific study is explained by the lack of a full-fledged legal framework and the need to develop an effective system of artificial intelligence legal regulation at both the national and international levels. The purpose of this article is to study the problems in the system of legal regulation of artificial intelligence in Ukraine and worldwide. The authors analyze approaches to the regulation of artificial intelligence in other developed jurisdictions, such as the European Union, the United States, Japan, and China. At the same time, this research article was based on the main positions of the negotiating position of the Artificial Intelligence Act, developed within the competence of the European Parliament, in order to understand the systemic societal considerations arising from the introduction of artificial intelligence into technology and society. As a result of the study, the authors characterize the areas of legal regulation of the artificial intelligence phenomenon in the context of leading countries of the world, identifying the main objectives of the law-making process in the context of ensuring intellectual security, and, accordingly, formulate conclusions and provide recommendations for improving the aforementioned intellectualization apparatus and forming a system of legal regulation in the field of artificial intelligence in Ukraine. The article focuses on identifying gaps in the current system of legal regulation of artificial intelligence. At the same time, the authors conclude that states have not yet come to a definitive position on how artificial intelligence should be governed, and its regulation is currently driven by corporate interests and supported by an ethical approach. Therefore, there is definitely an urgent need for unified legal and regulatory frameworks for artificial intelligence to prevent systemic and social risks in the field of intellectual security.